Family Experiments: Middle-class, professional families in Australia and New Zealand c. 1880-1920 - Richardson, Shelley (ANU Press, 2016)
Family Experiments explores the forms and undertakings of 'family' that prevailed among British professionals who migrated to Australia and New Zealand in the late nineteenth century. Their attempts to establish and define 'family' in Australasian, suburban environments reveal how the Victorian theory of 'separate spheres' could take a variety of forms in the new world setting. The attitudes and assumptions that shaped these family experiments may be placed on a continuum that extends from John Ruskin's concept of evangelical motherhood to John Stuart Mill's rational secularism. Central to their thinking was a belief in the power of education to produce civilised and humane individuals who, as useful citizens, would individually and in concert nurture a better society. Such ideas pushed them to the forefront of colonial liberalism. The pursuit of higher education for their daughters merged with and, in some respects, influenced first-wave colonial feminism. They became the first generation of colonial, middle-class parents to grapple not only with the problem of shaping careers for their sons but also, and more frustratingly, what graduate daughters might do next.